DETERMINAN AUDIT DELAY DAN PENGARUHNYA PADA HARGA SAHAM - Sitanggang, Arthur; Ariyanto, Dodik (E-Jurnal Akuntansi, 2015)
Timeliness of financial statements is an important thing because it can affect the assessment and the decision taken by the stakeholders. This research purposed to empirically examined the determinants of audit delay and its effect on stock prices. Total of 88 companies obtained using purposive sampling method to the companies listed in Indonesia Stock Exchange 2012-2013 period. The data analysis technique used is multiple linear regression and simple linear regression. Test results of multiple linear regression showed that the size of public accountant had a significant effect on audit delay, while the change of public accountant , profitability, and company size, had no effect on audit delay. Results of simple linear regression test showed that audit delay had no effect on stock prices.
Keywords: determinant of audit delay, audit delay, stock prices